2020
DOI: 10.1007/s00380-020-01634-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal pressure and its relationship with markers of congestion in patients admitted for acute decompensated heart failure

Abstract: Background: Systemic congestion is one of the mechanisms involved in acute decompensated heart failure (ADHF). Increased intraabdominal pressure (IAP), elicited by abdominal congestion, has been related to acute kidney injury and prognosis. Nonetheless, the link between diuretic response, surrogate markers of congestion and renal function remains poorly understood. Methods and results:We measured IAP in 43 patients from a non-interventional, exploratory, prospective, single center study carried out in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…65 Another study reported a similar association between increased IAP (≥12 mmHg) and renal dysfunction in patients with acute HF with mid-range ejection fraction and preserved ejection fraction. 66 Furthermore, in that study, a persistent increase in IAP at 72 h was associated with a longer length of hospital stay and 1 year mortality. 66 Microcirculatory disturbance occurs when IAP reaches 10-15 mmHg.…”
Section: Chronic Kidney Disease and Pulmonary Hypertensionmentioning
confidence: 69%
See 3 more Smart Citations
“…65 Another study reported a similar association between increased IAP (≥12 mmHg) and renal dysfunction in patients with acute HF with mid-range ejection fraction and preserved ejection fraction. 66 Furthermore, in that study, a persistent increase in IAP at 72 h was associated with a longer length of hospital stay and 1 year mortality. 66 Microcirculatory disturbance occurs when IAP reaches 10-15 mmHg.…”
Section: Chronic Kidney Disease and Pulmonary Hypertensionmentioning
confidence: 69%
“…66 Furthermore, in that study, a persistent increase in IAP at 72 h was associated with a longer length of hospital stay and 1 year mortality. 66 Microcirculatory disturbance occurs when IAP reaches 10-15 mmHg. 61 In animal models, renal dysfunction commences at IAP of 10 mmHg, 67,68 and anuria occurs at IAP of 30 mmHg.…”
Section: Chronic Kidney Disease and Pulmonary Hypertensionmentioning
confidence: 69%
See 2 more Smart Citations
“… 27) 28) In patients with acute decompensated HF, increased intraabdominal pressure was also prevalent and correlated with the serum creatinine level in patients who had HF with reduced left ventricular ejection fraction. 29) Another study reported that a persistent increase in intraabdominal pressure at 72 hours was associated with 1-year mortality and a longer length of hospital stay in patients who had acute HF with reduced ejection fraction and preserved ejection fraction. Furthermore, a strong correlation was observed between a reduction in the intraabdominal pressure at baseline and improvement in renal function, independent of hemodynamic changes.…”
Section: Pathophysiology Of Cardiorenal Syndromementioning
confidence: 99%